Short-course antidepressant therapy reduces discontinuation syndrome while maintaining treatment efficacy in patients with refractory functional dyspepsia: A randomized controlled trial - Wang, Qian-Qian; Cheng, Li; Wu, Bi-Yu; Xu, Ping; Qiu, Hong-Yi; Wang, Bo; Yan, Xiu-Juan; Chen, Sheng-Liang (Frontiers in Psychiatry, 2022)
Background and objective Long-course (LC) antidepressants for the treatment of disorders of gut-brain interaction, such as refractory functional dyspepsia (rFD), pose patients at risk of antidepressant discontinuation syndrome (ADS). Short-course (SC) therapy of rapid-acting antidepressant may reduce discontinuation syndromes while maintaining efficacy for dyspeptic symptoms. However, the evidence-based research is lacking. This study aims to determine whether SC therapy with antidepressants could decrease the risk of ADS with comparable treatment efficacy to LC therapy in rFD. Methods This randomized clinical trial with rFD patients was conducted at a tertiary hospital in China. Participants (N = 240) were randomly allocated to receive flupentixol-melitracen (FM) plus omeprazole therapy for 2 (SC group) or 4 (LC group) weeks, respectively. Scores for Leeds Dyspepsia Questionnaire (LDQ), Generalized Anxiety Disorder-7 (GAD-7) and Patient Health Questionnaire-9 for Depression (PHQ-9) were assessed at baseline and every 2 weeks, ending at 4 weeks after treatment. ADS was assessed after drug cessation. Medication possession ratio (MPR) for FM was calculated. Results The severity and incidence of ADS of patients in SC group were significantly lower than those in LC group (0.60 ± 0.62 vs. 1.71 ± 1.58 and 3.64 vs. 39.45%; both P < 0.0001). The MPR values for FM were significantly higher in patients of SC group than in LC group (P < 0.0001). Scores for LDQ, GAD-7 and PHQ-9 decreased in patients of both groups, and the symptom improvement in SC group was comparable to that in LC group after treatment. Conclusions Compared to 4-week FM therapy, the 2-week FM therapy reduces the risk of ADS with non-inferior treatment efficacy in patients with rFD. Clinical trial registration Clinical trials.gov, identifier NCT05099913.